Shielding Children From Nudity, But Not Violence ... Do Minors' First Amendment Rights Make Sense? - Vincent S. Onorato (Washington University Journal of Law & Policy, 2013)
Historically, children have been exposed to violence by authors and directors who have depicted violence as a central theme, whether it has been words within literature or visual images within movies. As technology has continued to evolve in the modern era, video games have surfaced as a new form of media. These video games, similar to literature and movies, have also seemed to place violence at the forefront, exposing children to even more violence. Yet, unlike literature and movies, the highly interactive nature of video games allows players to control the gruesome violence that occurs. This has led some states to question whether regulations need to be in place to censor children from exposure to this extreme violence. California is the most recent state to enact a statute aimed at protecting children from violent video games. Specifically, on October 7, 2005, then-California Governor Arnold Schwarzenegger signed into law Assembly Bill 1179 (“A.B. 1179”), codified at Civil Code §§ 1746–1746.5. In short, the law had the effect of labeling violent video games “adult only” and prohibited retailers from renting or selling them to anyone under age eighteen. In response to the proposed bill, the video game and software industries filed suit against the Governor, on the grounds that the Act violated the First Amendment. The suit led to the recent U.S. Supreme Court decision, Brown v. Entertainment Merchants Association. Part I of this Note begins by delving into the history of the First Amendment, beginning with what it looked like in the eyes of the framers to its current construction. Part I next explores the case law, which helped form the Supreme Court’s decision in Brown. Part II starts with an analysis of the case law used by the Supreme Court in Brown. It argues that the Court was incorrect both in its reasoning and ultimate holding that nudity and violence are to be judged by different standards with respect to minors. Part II closes by illustrating the problem of the current state of minors’ First Amendment rights as a result of Brown. Finally, Part III proposes two possible solutions the Supreme Court in Brown could have made to solve the inconsistency of minors’ First Amendment rights. The first possible solution is to apply the obscenity-for-minors standard from Ginsberg to violence, thereby eliminating the application of strict scrutiny. Accordingly, this solution suggests that violence be treated as obscenity for minors. The second possible solution is more extreme, advocating that the Supreme Court overrule its decision in Ginsberg, giving children and adults the same First Amendment rights.
Keywords: violence; minors; technology; video games; Brown v. Entertainment Merchants Association